Occupational Safety and Health Hazards among Smoked Fish Workers in Demak - Ekawati Ekawati; Yuliani Setyaningsih; Ida Wahyuni (Universitas Islam Bandung, 2022)
Smoked fish is an essential commodity in Central Java. Smoked fish workers must always ensure the availability of smoked fish products for the community. To work continuously, workers need to maintain their safety and health. Workers are constantly exposed to potential hazards from their work. This study aimed to describe the potential occupational hazards of smoked fish workers and identify efforts to control these hazards. This descriptive research involved smoked fish workers cleaning, cutting, washing, and smoking fishing in Demak city, Central Java, in March 2021. The job safety analysis (JSA) method was used to describe potential hazards in every work process. The results showed that the potential risks found in the working process of smoking fish were a wet and humid work environment, sharp work equipment, non-ergonomic work postures, and a hot work climate. It can be concluded that workers are exposed to various hazards in their work and work environment. Therefore, it is necessary to increase occupational safety and health (OSH) awareness and working environment conditions in the smoked fish industry so that workers will always be safe and healthy at work.